Associations between workload, myosin isoforms and performance on professional male basketball. A 4 seasons follow up - Guerrero, M.; Cadefau, J. A.; Rodas, G.; Cussó, R.; Caparros, T. (Apunts Sports Medicine, 2023)
The aim of this study was to determine associations between workload, myosin isoforms, and performance in professional basketball, by following the progress of a professional basketball team over four consecutive seasons. Thirty male professional basketball players (age, 27.6 ± 4.1 years;height, 200.1 ± 9.4 cm;weight, 98.5 ± 12.6kg) from an elite professional basketball team participated in this retrospective observational study. To analyze muscle response and which types of fiber were most involved, fast and myosin in serum were evaluated from three blood samples taken during the season, using enzyme-linked immunosorbent assay (ELISA). Parameters recorded were: exposure time,. Slow and fast myosins for muscle responses. Competitions won, ranking, and mean points scored for performance. Average values per season analysed were 280.1 ± 58 h of exposure to practice,1440.58±533.46µlmol/L of fast and 1178.75±427.75 µmol/L of slow myosin. Performance, assessed as team ranking was 6879.5 ± 985.37 u.a. per season and 90.72±2.79 u.a. per game, winning 7 competitions. Large negative relationships could be observed between slow myosins and exposure time (rho=-0.63;p=.02); There were possible associations between slow myosins and player mean performance per game (R2=0.98;p<.01) and team performance outcomes achieved (R2=0.83;p = 01) during these four seasons. Higher slow serum myosin values could be related to higher exposure time, and lower slow serum myosin values could be associated with better player and team performance